Gambaran Konsep Diri pada Atlet LGBT di Sidoarjo - Arum, Adelia; Hazim, Hazim (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Often, the people around him view a person's orientation negatively. Lesbian sexual orientation is one of the sexual orientations that usually receives a negative stigma, which can influence the self-perception of the individual concerned. This research aims to find out how the self-concept of LGBT individuals is currently widespread in society. The research sampling technique used a purposive sampling technique with the criteria that the subjects were LGBT individuals, especially female athletes who had a lesbian sexual orientation aged 20-23 years and lived in Sidoarjo. The number of samples used in this research consists of 2 research subjects and two significant others to validate information from research subjects. This research uses triangulation methods with the data analysis technique used in this research, namely, descriptive analysis techniques and flow models. The results showed that both subjects had a negative self-concept picture. This is demonstrated by rejection of self-acceptance, negative thoughts about oneself, lack of definite goals and direction in life, and poor relationships with family. It's just that the second subject has differences in the goals and direction of a good life.